Teachers’ Perceptions of Using Language Games - Linda Mayasari (Muhammadiyah University of Mataram, 2019)
This paper focuses on analyzing teachers’ perspective of using language games. The subjects were eleven English teachers who teach at Muhammadiyah junior and senior high school located in Surabaya. They were taken by using proportional stratified random sampling. The details were seven from Muhammadiyah junior high schools and four from Muhammadiyah senior high schools. This research took one English teacher from each school. The research instruments were questionnaire and interview. Based on data analysis, it gathered several results; first the teachers prefer non digital language games. Second, if they apply language games in pre teaching, they become as “a bridge” to the new topic being discussed. When the teachers hold language game in the post teaching activity, the purpose is to check the students’ comprehension. The teachers agree that language games give positive insights toward the students in learning English. However, these also bring some problem – the need of using L1 for students to understand how they run the language games and to win the game.